Cross-Cultural Literacy Experiences in High School in Canada: Two Multilingual Learners’ Retrospective Accounts - Ahn, Sung Kyung (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
This study examines multilingual high school students’ responses to social studies assignments as a window into their content area literacy experiences in Canadian schools. Data for this study are drawn from two qualitative case studies which produced retrospective accounts for two multilingual learners who had completed high school in Alberta. The participants were undergraduate students at a reputable Canadian university when they participated in the research. The study highlights what was challenging for the students and how their efforts in written assignments took direction from what their teachers emphasized. The students’ perspectives on their experiences with the content area writing in social studies can inform thinking about related instruction and research.